Patient–therapist convergence in alliance ratings as a predictor of outcome in psychotherapy for generalized anxiety disorder. (2nd November 2018) - Coyne, Alice E.; Constantino, Michael J.; Laws, Holly B.; Westra, Henny A.; Antony, Martin M.
Abstract: Objective: Although patients and therapists aligning over time on their perceptions of alliance quality is regarded as clinically important, few studies have examined the influence of such dyadic convergence on psychotherapy outcomes. This study tested whether early treatment convergence in patient–therapist alliance ratings was associated with subsequent worry and distress reduction in psychotherapy for generalized anxiety disorder (GAD), and whether treatment type and the dyad members' initial alliance perceptions moderated these associations.Method: Data derived from a randomized trial for which patients with severe GAD received either 15 sessions of standard cognitive-behavioral therapy (CBT; n  = 43) or CBT integrated with motivational interviewing ( n  = 42). Patients and therapists rated the alliance after each session. Patients rated worry after each session, and their distress multiple times.Results: As predicted, dyadic multilevel modeling revealed that early alliance convergence was associated with greater subsequent worry ( p  = .03) and distress ( p  = .01) reduction, and the combination of low initial patient-rated alliance and low convergence was associated with the worst outcome for the distress variable ( p  = .04).Conclusions: Results suggest that alliance convergence may be an important clinical process that bears on outcome, rendering it an important marker for therapist responsiveness.